Mobile Application for Children With Learning Difficulties In Mathematics - An Exploratory Study - Dhiviya Gopal, Balakrishnan (Universiti Malaysia Sarawak (UNIMAS), 2020)
Word problems are mathematics questions in the form of sentences. A good understanding of word-problems is important because it enables children to answer complex questions more easily. This study focused on the performance of students with mathematics learning difficulties in word-problems. The participants were comprised of ten 9-year-old children (4 females and 6 males). These children were then randomly divided into experimental group and the control group. The intervention group received the Wordie Problem mobile application intervention where else the control group did not receive any. Mann Whitney U test was used to analyse differences in the performance of the two groups. The participants in the intervention group showed an improvement after the intervention of mobile application was completed. However, there was a significant difference in the student’s engagement to learn mathematics. Hence, mobile application was found to be effective for children in learning word problem questions.